Metabolites Profiling and Bioassays Reveal Bassia indica Ethanol Extract Protective Effect against Stomach Ulcers Development via HMGB1/TLR-4/NF-κB Pathway - Zeinab A. El-Gendy; Rehab F. Taher; Abdelbaset M. Elgamal; Ahmed Serag; Azza Hassan; Gehad A. Abdel Jaleel; Mohamed A. Farag; Abdelsamed I. Elshamy (MDPI AG, 2023)
Clinical manifestation of gastric ulcers is frequent, in addition to their costly drug regimens, warranting the development of novel drugs at lower costs. Although Bassia indica is well characterized for its anti-inflammatory and antioxidant potential, capacity of its ethanol extract (BIEE) to prevent stomach ulcers' progression has not been reported. A nuclear protein termed high-mobility group box 1 (HMGB1) plays a key role in the formation of stomach ulcers by triggering a number of inflammatory responses. The main purpose of the current investigation was to evaluate the in vivo anti-inflammatory and anti-ulcerogenic capabilities of BIEE against ethanol-induced gastric ulcers in rats via the HMGB1/TLR-4/NF-B signaling pathway. HMGB1 and Nuclear factor kappa (NF-B) expression, IL-1β and Nrf2 contents showed an increase along with ulcer development, concurrent with an increase in immunohistochemical TLR-4 level. In contrast, pre-treatment with BIEE significantly reduced HMGB1 and Nuclear factor kappa (NF-B) expression levels, IL-1β and Nrf2 contents and ulcer index value. Such protective action was further confirmed based on histological and immunohistochemical TLR-4 assays. Untargeted analysis via UPLC-ESI-Qtof-MS has allowed for the comprehensive characterization of 40 metabolites in BIEE mostly belonged to two main chemical classes, viz., flavonoids and lipids. These key metabolites, particularly flavonoids, suggesting a mediation for the anti-inflammatory and anti-ulcerogenic properties of BIEE, pose it as a promising natural drug regimen for treatment of stomach ulcers.